Constructicography : Constructicon Development Across Languages. - Lyngfelt, Benjamin; Borin, Lars.; Ohara, Kyoko; Torrent, Tiago Timponi (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2018)
This is the first major publication devoted to constructicon development and it should be particularly relevant for those interested in construction grammar, frame semantics, lexicography, the relation between grammar and lexicon, or linguistically informed language technology.
4. Prospects for multilingual constructicography -- 4.1 Computational alignment -- 4.2 Resources for human users -- 5. Concluding remarks -- Acknowledgments -- References -- Appendix. Summary of the contrastive analyses -- General index -- Index of constructions.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books